Cross-sectional age differences in dispositional optimism in Chinese children and adolescents. (November 2016) - Zou, Rong; Zhang, Dong-Jing; Niu, Geng-Feng; Xie, Xiao-Chun; Fan, Cui-Ying; Tian, Yuan; Zhou, Zong-Kui
Abstract: Research has demonstrated the important roles of dispositional optimism played in individuals' life quality. But little is known about age differences in dispositional optimism especially in late childhood and adolescence. This study examined age differences in dispositional optimism in Chinese children and adolescents ( N  = 2738; M age  = 12.75 years; SD  = 2.53; age range 9–19). Results revealed that the bi-dimensional structure of dispositional optimism (i.e., optimism and pessimism) was similar in each grade. Optimism had a negative linear pattern with age. Pessimism decreased from strongly to weakly, showing a curvilinear pattern with age. Overall optimism (representing the presence of optimism and the lack of pessimism) had a positive linear relationship with age. Moreover, only the development of pessimism was moderated by gender and family socioeconomic status. These findings suggest that dispositional optimism varies by age, and that optimism and pessimism are partially independent. Highlights: Examined age trends in dispositional optimism in a large sample The bi-dimensional structure of dispositional optimism was similar in each grade. Optimism had a negative linear pattern with age. Pessimism had a cubic pattern with age, moderated by gender and socioeconomic status. Overall optimism had a positive linear pattern with age.